Strengthening economic resilience through ICT during the COVID-19 pandemic: evidence from 100 countries - Muhammad Bilal; Sohaib Aqib; Ahmad Raza (Discover Sustainability)
Abstract Amidst COVID-19 related confinement measures, economies worldwide have transitioned to online platforms, making ICT essential for sustaining economic activities. This study investigates the role of ICT in mitigating the negative economic impact of the COVID-19 pandemic. We employed a comprehensive ICT index developed by UNCTAD, including indicators such as fixed broadband, mobile phone subscriptions, and secure internet servers, using data from 100 countries between 2017 and 2022. Utilizing Generalized Method of Moments (GMM) estimation to address endogeneity, our analysis reveals that a percentage increase in COVID-19 cases and deaths led to declines in GDP growth by 0.67 and 0.87 percentage points, respectively. However, ICT significantly alleviated the adverse economic effects of the pandemic. The negative impact was more severe in developing countries, where ICT played a crucial role in mitigation. These findings suggest important policy implications, highlighting the need for increased ICT investment and capacity building to enhance economic resilience against future crises.